Electrochemically active iron (III)‐reducing bacteria in coastal riverine sediments. (26th September 2017) - Zheng, Shiling; Wang, Bingchen; Li, Ying; Liu, Fanghua; Wang, Oumei
Abstract : Iron (III)‐reducing bacteria (IRB) play significant roles in the degradation of naturally occurring organic matter and in the cycling of heavy metals in marine and freshwater sediments. Our previous study has demonstrated the co‐occurrence of Geobacteraceae and Methanosarcinamazei as aggregates in the iron (III)‐reducing enrichments from a coastal gold mining site on the Jiehe River. The IRB community in the enriched sediments was dominated by members of Comamonadacea, Clostridiaceae, Bacillaceae, Bacteroidaceae, and Geobacteraceae . Furthermore, four representative strains (JhA, JhB, JhC‐1, and JhC‐2) were isolated and found to belong to the genus of Anaerosinus, Bacillus, and Clostridium with 97.31–98.82% identity of 16S rRNA genes. The iron (III)‐reducing ability of all these isolates was identified. Interestingly, JhA showed electrochemical activity with chronoamperometry (CA) and cyclic voltammetry (CV), indicating its ability to oxidize ethanol, liberate, and transfer electrons, thus, expanding our knowledge of a new genus with electrochemical activity. The results revealed the cultivability and electrochemical activity of IRB in coastal riverine sediment and indicated that JhA was an unknown extracellular electron producer with the ability to reduce iron (III). This study expands our knowledge of the electrochemical characterization of the genus Anaerosinus . It is reasonable to expect that these isolates have potential applications in heavy metal bioremediation operations in natural environments.